Faktor-Faktor Keuangan Yang Memengaruhi Manajemn Laba - Anita Wijaya Ningsih; Rieka Ramadhaniyah; Nolita Yeni Siregar; Reva Meiliana; Dedi Putra (Universitas Bandar Lampung (UBL), 2021)
This study aims to examine financial factors such as profitability, leverage, firm size and book tax difference on earnings management. The samples used were 61 samples of manufacturing companies obtained for 3 years from 2017-2019 by purposive sampling method. The data analysis technique used is multiple linear regression analysis. This research has succeeded in proving that the difference between book tax and profitability has an effect on earnings management; Meanwhile, Leverage and firm size have no effect on earnings management.